NMR investigations on binding and dynamics of imidazolium-based ionic liquids with HEWL. Issue 41 (19th October 2020) - Reddy, R. Ravikanth; Reddy, Jithender G.; Kumar, B. V. N. Phani
Abstract : Ligand and protein-based approaches depicting the interaction of IL with HEWL. Abstract : Molecular level insights on protein–ionic liquid (P–IL) interactions are beneficial for assessing protein stability, binding and dynamics. In the present work, interactions of ILs, namely, 1-butyl 3-methylimidazolium methyl sulfate (IL1), 1-butyl 3-methylimidazolium octyl sulfate (IL2) and 1-butyl 3-methylimidazolium chloride (IL3) with hen egg white lysozyme (HEWL) protein were investigated using solution-state nuclear magnetic resonance (NMR) spectroscopy. To ascertain the binding and dynamics from the perspective of both protein and IL, various ligand based NMR approaches such as selective and non-selective nuclear spin-relaxation ( R 1SEL and R 1NS ), saturation transfer difference (STD), difference of inversion recovery rate with and without target irradiation (DIRECTION), 35 Cl line-shape and spin-relaxation, and protein back bone amide chemical shift perturbations (CSPs) from 1 H– 15 N HSQC were utilized. Among the ILs investigated, IL2 experiences significant interaction relative to those of IL1 and IL3, as revealed by the combined R 1SEL and R 1NS analysis, which is further supported by STD NMR. CSP analyses of 1 H– 15 N HSQC spectra of aqueous P–IL mixtures enabled to identify the potential binding sites of ILs with HEWL. Whereas, 15 N longitudinal ( R 1 ) and transverse ( R 2 ) spin-relaxation rates and 15 N{ 1 H} heteronuclear nuclear Overhauser effect (hetNOE) data subjected to the model free analysis for IL2 yielded the rotational correlation times and order parameters of various residues of HEWL. Furthermore, the results could discern the nature of interactions between studied ILs and HEWL in terms of specific and non-specific interactions.